THE IMPACTS OF DIFFERENT LEARNING INTENSITIES ON KINESTHETIC EFL STUDENTS’ SPEAKING PERFORMANCE - Dedi Aprianto; Sutarman Sutarman (Universitas Wiralodra, 2025)
The study investigated the impacts of high, moderate, and low learning intensities on kinesthetic learners’ speaking performance in the Bachelor of English Literature program at Bumigora University. Using a quantitative research design, 42 kinesthetic learners were identified through a VARK questionnaire and a validated learning intensity questionnaire, categorizing them into three intensity groups. Speaking performance was assessed based on fluency, pronunciation, vocabulary, coherence, and task fulfillment. Data collection included administering both questionnaires and conducting speaking tests. One-Way ANOVA analysis revealed significant differences in speaking performance, with the high-intensity group achieving the highest mean score (91.38), followed by moderate (82.00) and low-intensity groups (70.21). The results confirmed these differences (Sig. 0.000 < 0.05), and Post-hoc analysis indicated that the high-intensity group significantly outperformed the moderate and low groups, with mean differences of 9.385 and 21.174, respectively (Sig. 0.000 < 0.05). The moderate group also significantly surpassed the low group with a mean difference of 11.789 (Sig. 0.000 < 0.05). These findings suggest pedagogical implications for developing instructional strategies to enhance EFL speaking performance among kinesthetic learners. Higher learning intensity significantly improves speaking performance, and further research could explore its effects on other learning styles such as auditory or visual.